The relationship of breast density in mammography and magnetic resonance imaging in women with triple negative breast cancer. Issue 124 (March 2020) - Mema, Eralda; Schnabel, Freya; Chun, Jennifer; Kaplowitz, Elianna; Price, Alison; Goodgal, Jenny; Moy, Linda
Highlights: Women with lower mammographic density had 2.53- fold increased odds of having TNBC. Women with lower FGT on breast MRI had 5.73-fold increased odds of having TNBC. Women with lower MRI BPE had more than a two-fold increased odds of having TNBC. Abstract: Purpose: To evaluate the relationship between mammographic density, background parenchymal enhancement and fibroglandular tissue on MRI in women with triple negative breast cancer (TNBC) compared to women with non-triple negative breast cancer (non-TNBC). Methods: The institutional Breast Cancer Database was queried to identify the clinicopathologic and imaging characteristics among women who underwent mammography and breast MRI between 2010-2018. Statistical analyses included Pearson's Chi Square, Wilcoxon Rank-Sum and logistic regression. Results: Of 2995 women, 225 (7.5 %) had TNBC with a median age of 60 years (23–96) and median follow-up of 5.69 years. Compared to women with non-TNBC, TNBC was associated with African-American race 36/225 (16 %), BRCA1, 2 positivity 34/225 (15.1 %), previous history of breast cancer 35/225 (15.6 %), presenting on breast exam 126/225 (56 %) or MRI 13/225 (5.8 %), palpability 133/225 (59.1 %), more invasive ductal carcinoma (IDC) 208/225 (92.4 %), higher stage (stage III) 37/225 (16.5 %), higher grade (grade 3) 186/225 (82.7 %) (all p < 0.001), lower mammographic breast density (MBD) 18/225 (8 %) (p = 0.04), lower fibroglandular tissue (FGT) 17/225 (7.6 %) (p = 0.01), and lower background parenchymal enhancement (BPE) 89/225 (39.8 %) (p = 0.02). Nine of 225 (4 %) women with TNBC experienced recurrence with no significant association with MBD, FGT, or BPE. There was no significant difference in median age of our TNBC and non-TNBC cohorts. Conclusions: The higher proportion of women with lower MBD, FGT and BPE in women with TNBC suggests that MBD, amount of FGT and degree of BPE may be associated with breast cancer risk in women with TNBC.